Netizens' Opinions on the "Boycott Misleading Horror Movies" Action on Social Media Instagram - Syahrul Ramadhan; Nur Maghfirah Aesthetika; Helmy Muhammad; Nur Aini Shofiya Asy'ari (ETTISAL : Journal of Communication, 2024)
This study aims to analyze netizen responses to the boycott of horror films that use religious symbols on Instagram social media, as well as identify factors that influence netizen behavior after watching the film. This research uses a qualitative method with a content analysis approach and a netnography study. The results show that the majority of netizens support the boycott of films that are considered misleading and damaging to the faith, with the film Â«KiblatÂ» as one example that is considered to harass Islamic symbols.Â Netizensâ€º reactions are influenced by various factors, including social factors,Â personality,religiosity, age, and the roleÂ of social media. Instagram, as the main platform, allowed netizens to express their opinions regarding the boycott of this horror movie,Â which shows that social media has an important role in shaping public opinion and can have a significant impact on the film industry in Indonesia. Netizensâ€º negative reactions to the use of religious symbols in horror films reflect a high sensitivity to religious issues, especially when they are perceived to undermine faith values. This research provides important insights into how religious symbols in horror films can trigger widespread social reactions among social media users, as well as how such reactions can influence trends in the creative industry in Indonesia, particularly in the production of films involving religious elements.